EXPLICATING POETRY TO DESCRIBE THE POSSIBLE MEANING OF A POEM - Feriyanti Elina Gultom (BAHAS, 2017)
Poetry is the literature that evokes a concentrated imaginative awareness of experience or a specific emotional response through language chosen and arranged for its meaning, sound, and rhythm. There are feelings, thoughts, and ideas that can be difficult to explain and analyze. Poetry is a kind of language within languages that allows people regardless of age, sex, religion, sexual orientation, and even time eras to communicate with one another. When some people hear the word